Characterization and management of subcapsular hepatic hematoma in women with preeclampsia and HELLP syndrome - Guevara-Rios, Enrique (2022)
Introduction. Maternal mortality is higher in developing countries, due to complications of pregnancy and / or the puerperium; liver rupture being the most catastrophic complication. Objective. To describe the characterization and management of subcapsular hepatic hematoma in patients with preeclampsia with criteria of severity and HELLP syndrome. Methods. Observational and descriptive study, carried out at the National Maternal Perinatal Institute of Peru, between 2003 and 2020. Patients with preeclampsia with severity criteria and HELLP syndrome who presented subcapsular hepatic hematoma participated. Information was collected from the clinical history. Descriptive statistics were used in the data analysis. Results. In the study period, 53 patients with subcapsular hematoma were identified from 342,000 deliveries attended. 37.7% were pregnant and 62.3% puerperal, the most frequent symptoms being upper abdominal pain and headache. Surgical treatment was performed by laparotomy and packing of the liver in 94.3%. The most frequent complications were multiple organ failure, hypovolemic shock, and acute renal failure. A survival rate of 81% of patients was observed. Conclusion. An incidence of 1.65 cases x 10,000 deliveries and a mortality of ten cases (19%) was evidenced. The identification of subcapsular hematoma should be suspected in those pregnant women with preeclampsia with severity criteria that present symptoms of epigastric pain and headache, being more frequent in the postpartum period. Laparotomy and liver packing along with volume replacement contribute to the management of these patients, which should be performed promptly in unstable patients.